2024
DOI: 10.1002/adma.202312497
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Functional Responses in Astrocytes under Alternating Deformation Modes Using Magneto‐Active Substrates

Clara Gomez‐Cruz,
Miguel Fernandez‐de la Torre,
Dariusz Lachowski
et al.

Abstract: This work introduces NeoMag, a system designed to enhance cell mechanics assays in substrate deformation studies. NeoMag uses multidomain magneto‐active materials to mechanically actuate the substrate, transmitting reversible mechanical cues to cells. The system boasts full flexibility in alternating loading substrate deformation modes, seamlessly adapting to both upright and inverted microscopes. The multidomain substrates facilitate mechanobiology assays on 2D and 3D cultures. The integration of the system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Astrocytes, like other cells, respond to physical changes in the extracellular matrix (ECM) by converting structural changes of the parenchyma into intracellular signals through a process known as mechanotransduction ( Chen and Qiu, 2022 ; Donnaloja et al, 2023 ). Extreme mechanical stress may be exerted on parenchymal fluid routes in a variety of pathologies, like TBI ( Gomez-Cruz et al, 2024 ), and could potentially contribute to the reduced glymphatic transport observed in fluidopathies. Astrocyte endfeet are particularly sensitive to shear forces of ISF flux driven by vascular pulsatility, especially where the BBB is compromised and flow velocity is reduced ( Momin et al, 2021 ).…”
Section: The Glymphatic Systemmentioning
confidence: 99%
“…Astrocytes, like other cells, respond to physical changes in the extracellular matrix (ECM) by converting structural changes of the parenchyma into intracellular signals through a process known as mechanotransduction ( Chen and Qiu, 2022 ; Donnaloja et al, 2023 ). Extreme mechanical stress may be exerted on parenchymal fluid routes in a variety of pathologies, like TBI ( Gomez-Cruz et al, 2024 ), and could potentially contribute to the reduced glymphatic transport observed in fluidopathies. Astrocyte endfeet are particularly sensitive to shear forces of ISF flux driven by vascular pulsatility, especially where the BBB is compromised and flow velocity is reduced ( Momin et al, 2021 ).…”
Section: The Glymphatic Systemmentioning
confidence: 99%